ACETAZOLAMIDE IS A MEDICINE FOR THE MEDICATED CORRECTION OF THE SLEEP APNEA AND HYPOPNEA SYNDROME AMONG CHILDREN AND ADULTS - O.V. Bykova; L.M. Kuzenkova; O.I. Maslova; A.N. Boyko (Вопросы современной педиатрии, 2006)
Sleep apnea and hypopnea syndrome is a life bendangering sleep dis order among both adults and children. The prevalence of the sleep apnea and hypopnea syndrome both in adult and pediatric population may be evaluated only approximately, as not all of the patients, suffering from this pathology, may call some adequate complaints, which, in their turn, help diagnose the disease. For example, only obstructive sleep apnea syndrome according to the data of British epidemiologists is met among the adults at the frequency rate, which can be compared with the prevalence of the bronchial asthma. Since metabolic acidosis caused by the carbonic anhydrase inhibitor of acetazolamide stimulates the ventilation of lungs, the researchers have set forth a supposition that the application of this medicine can be efficient to treat the respiratory disturbances in sleep. There is wide application of acetazolamide for the medicated correction of sleep apnea and hypopnea syndrome of the central genesis among both adults and children. When using acetazolamide for the long term therapy of respiratory disturbances among adult patients, the main issue is the probable growth of tolerance towards the carbonic anhydrase inhibitor along with the continuous longbterm application of the medicine. In pediatry, quite on the contrary, the sleep apnea and hypopnea syndrome is usually a transit problem of the early infancy and it does not require any longbterm drug therapy, which defines specifically high perspectives of the efficient and safe application of acetazolamide for the medicated correction of respiratory disturbances in sleep precisely within this category of patients.Key words: apnea, hypopnea, sleep disorder, acetazolamide, children.